Penerapan Trayek Pembelajaran, Media Pembelajaran Menggunakan Papan Peluang, Dadu, dan Multimedia Pembelajaran Interaktif dengan Pendekatan RME di SMA Negeri 12 Medan - Manalu, Jhonatan; Kembaren, Shaerleen Naviry Br; Hutagalung, Chindy Fransiska; Sinurat, Relly; Kairuddin, Kairuddin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study examines the use of learning media such as probability boards, dice, and interactive multimedia with the Realistic Mathematics Education (RME) approach at SMA Negeri 12 Medan. The primary goal is to enhance students' understanding of probability concepts, which are often considered abstract and challenging. The research employs a descriptive quantitative method, with data collected through observations, interviews, student satisfaction surveys, and tests using Student Worksheet (LKPD). The findings indicate that the use of these media significantly improves students' understanding, with 85.71% of students achieving high to very high levels of comprehension. Moreover, most students stated that this method made it easier for them to grasp the material in a clearer, more relevant, and applicable manner. Thus, the application of RME-based learning media has proven effective in enhancing student engagement and understanding of probability concepts.